Effects of multicell beamforming on downlink data services in cellular CDMA. (1st October 2010) - Dhar Roy, Sanjay; Kundu, Sumit
This paper proposes and evaluates a scheme of combining multicell beamforming, power control, soft handoff in physical layer and automatic repeat request (ARQ) in link layer for improving the performance of data service in forward link of cellular CDMA. The present paper also proposes a scheme of beamforming-based power control scheme in physical layer for forward link of cellular CDMA. Beamforming has been assumed at three base stations (BSs) in our system model. A stop and wait ARQ scheme has been assumed for forward link data service. Joint effects of beamforming, power control, number of retransmission and soft handoff via cross-layer interaction reduce delay, bit error rate (BER) and increase throughput significantly. Impacts of several parameters of soft handoff, power control and beamforming and their cross-layer interaction on data performance have been evaluated. Both the cases of perfect and imperfect beamforming have been investigated. Effects of direction of arrival (DOA) estimation error associated with beamforming have also been indicated on data service.